Case Report: A rare case of synchronous ovarian mixed germ cell tumor and mast cell leukemia in a pediatric patient - Liu, Chengzhu; Chu, Jinhua; Wan, Yang; Wang, Huiping; Yu, Hongzhen; Zhang, Kunlong; Xie, Zhiwei; Tu, Songji; Wang, Ningling; Yang, Linhai (Frontiers in Oncology, 2026)
Patients with concurrent malignancies pose significant diagnostic and therapeutic challenges. We report a rare and fatal case of synchronous ovarian mixed germ cell tumor and mast cell leukemia (MCL) in a 13-year-old female, characterized by a shared clonal origin. The patient initially presented with a large pelvic mass, elevated alpha-fetoprotein(AFP) and human chorionic gonadotropin (β-HCG), anemia, and thrombocytopenia. Exploratory laparotomy confirmed a diagnosis of mixed germ cell tumor, predominantly dysgerminoma with a minor choriocarcinoma component. Despite an initial decrease in serum tumor markers to platinum-based chemotherapy, persistent cytopenias and bone marrow infiltration raised concern for hematologic malignancy. Genomic analyses of both ovarian tumor and bone marrow samples identified identical somatic mutations, including KIT D816V, NRAS G12C and TP53 Y220C, strongly suggesting a common progenitor. Subsequent immunophenotyping, histology, and transcriptome sequencing confirmed the diagnosis of concurrent mast cell leukemia. Targeted therapy with avapritinib and ruxolitinib was initiated but yielded limited response. Further salvage therapy failed due to disease progression and treatment intolerance, and the patient succumbed to multiple organ failure. This case underscores the clinical and genetic overlap between germ cell tumors and hematological malignancies in pediatric patients, highlighting the role of KIT mutations as a potential unifying driver. Given the consistent co-occurrence of KIT mutations in previously reported similar cases, we propose the recognition of a distinct disease entity: ovarian germ cell tumor/mastocytosis with KIT mutations. This report emphasizes the importance of early genetic profiling and multidisciplinary collaboration in diagnosing and managing rare, genetically unified malignancies in pediatric oncology.